Development of TaqMan RT-qPCR for the detection of regulated citrus viruses and viroids in Aotearoa New Zealand - Yan, Juncong; Tang, Joe; Perez-Egusquiza, Zoila; Thompson, Jeremy R. (Journal of virological methods, 2024)
The major citrus species include several economically important fruits, such as orange, mandarin, lemon, limes, grapefruit and pomelos. Since the 1980 s, total production and consumption of citrus has grown strongly with the current annual worldwide production at over 105 million tonnes. New Zealand's citrus exports, for instance, had an estimated worth of NZ$ 11.6 million (approx. US$ 7 million) in 2020. Citrus plants are prone to viral diseases, which can lead to substantial economic losses. In New Zealand, the citrus Import Health Standard (IHS) has identified 22 viruses and viroids that are subject to regulation and requires citrus nursery stock to be free of these pathogens. As such, there is a need for reliable, sensitive, and rapid detection methods to screen for these viruses and viroids during post entry quarantine. In this study, we developed TaqMan RT-qPCR assays for the detection of nine of these regulated viruses and viroids, namely citrus leaf rugose virus (CiLRV), citrus leprosis virus C (CiLV-C), citrus leprosis virus C2 (CiLV-C2), citrus leprosis virus N (CiLV-N), citrus psorosis virus (CPsV), citrus yellow mosaic virus (CYMV), citrus bent leaf viroid (CBLVd), citrus viroid V (CVd-V), and citrus viroid VI (CVd-VI). These assays have been validated and found to be highly sensitive, specific, and reliable. The implementation of these assays will facilitate the safe importation of citrus nursery stock, thus safeguarding the country's horticultural and economic interests. •New TaqMan RT-qPCR assays for the detection of nine emerging Citrus viruses and viroids.•Assays developed using latest global sequence data to ensure detection of all known isolates.•Validated assays with high sensitivity, specificity, and reliability.•Assays duplexed without loss in performance to include a plant internal control (Nad5).